2003
DOI: 10.1046/j.1442-2042.2003.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum prostate‐specific antigen in hemodialysis patients

Abstract: Background : The value of serum prostate-specific antigen (PSA) screening was examined to detect prostate cancer in men receiving hemodialysis. Methods : Forty-one male patients age 60-95 (median age, 70 years) receiving hemodialysis were investigated for PSA levels. We set the cut-off point at 4 ng/mL (the usual reference range). Digital rectal examination (DRE) and transrectal ultrasonography (TRUS) of the prostate were performed in patients whose PSA was more than 4 ng/mL and/or who expected further examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It was reported that the serum levels of AFP, CA 153 and PSA in CKD patients did not differ significantly compared with normal population [2,3,[5][6][7][8][9]. Our results were consistent with their findings.…”
Section: Effect Of Renal Function On Serum Concentrations Of Tumor Masupporting
confidence: 96%
“…It was reported that the serum levels of AFP, CA 153 and PSA in CKD patients did not differ significantly compared with normal population [2,3,[5][6][7][8][9]. Our results were consistent with their findings.…”
Section: Effect Of Renal Function On Serum Concentrations Of Tumor Masupporting
confidence: 96%
“…Screening for prostate cancer is widespread, with a greater prevalence of prostate cancer in the general population, although this type of screening is used rarely in patients with ESRD [1]. Although there is reportedly a greater risk of prostate cancer on PSA screening in patients with ESRD, and levels of PSA and associated markers in patients on dialysis have been reported, most studies were too small to obtain accurate findings [9][10][11][12][13][14]. The present findings suggested that the serum PSA level was higher in the ESRD than in the control group, and among men with PSA levels of > 10 ng/mL the cancer detection rate was higher in the ESRD than in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…In this series as well, prostate biopsy was recommended for patients with serum PSA of >4.0 ng/ml, and prostate cancer was detected in five of eight patients on hemodialysis undergoing prostate biopsy; that is, the rate of positive prostate biopsy in these patients was 62.5%, which is extremely high despite the lack of significant difference compared to that in men participating in a PSA mass screening test. Some previous studies also presented a high rate of positive prostate biopsy in patients with end-stage renal disease [13,16]. For example, Wada et al reported that prostate biopsy was performed in 26 patients on hemodialysis whose serum PSA of >4.0 ng/ml, and that 13 of these patients (i.e., 50.0%) were diagnosed as having prostate cancer [16].…”
Section: Discussionmentioning
confidence: 94%
“…Some previous studies also presented a high rate of positive prostate biopsy in patients with end-stage renal disease [13,16]. For example, Wada et al reported that prostate biopsy was performed in 26 patients on hemodialysis whose serum PSA of >4.0 ng/ml, and that 13 of these patients (i.e., 50.0%) were diagnosed as having prostate cancer [16]. Furthermore, in this series, the cancer detection rate in patients on hemodialysis was significantly greater than that in those participating in a PSA mass screening test.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation